2017
DOI: 10.1097/aap.0000000000000617
|View full text |Cite
|
Sign up to set email alerts
|

Residual Enoxaparin Activity, Anti-Xa Levels, and Concerns About the American Society of Regional Anesthesia and Pain Medicine Anticoagulation Guidelines

Abstract: Currently, the American Society of Regional Anesthesia and Pain Medicine (ASRA) anticoagulation guidelines recommend that before the performance of a neuraxial procedure a minimum of 24 hours should elapse following a treatment dose of enoxaparin (1 mg/kg twice daily or 1.5 mg/kg once daily). The guidelines have since their inception also consistently recommended against the routine use of anti-Xa level monitoring for patients receiving enoxaparin. However, we noted in our clinical practice that anti-Xa levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Even after waiting nearly 36 hours, more than 10% of patients still had levels of anti-Xa activity within the prophylactic range. Our findings are in line with a previous work conducted by Henshaw et al 8. In their report, 11 of 19 (57.9%) patients showed elevated anti-Xa levels within prophylactic range despite an interval of 24 hours after receiving therapeutic dose enoxaparin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Even after waiting nearly 36 hours, more than 10% of patients still had levels of anti-Xa activity within the prophylactic range. Our findings are in line with a previous work conducted by Henshaw et al 8. In their report, 11 of 19 (57.9%) patients showed elevated anti-Xa levels within prophylactic range despite an interval of 24 hours after receiving therapeutic dose enoxaparin.…”
Section: Discussionsupporting
confidence: 93%
“…After four to five half-lives, the residual activity of LMWH should be sufficiently decreased, in theory, allowing neuraxial blockade to be performed without a significant increased risk of bleeding 5. While the time interval has been well proven to be reasonably safe for prophylactic dosing of LMWH,7 there is doubt if these pharmacokinetic based time intervals are really sufficient for patients receiving therapeutic anticoagulation 8…”
Section: Introductionmentioning
confidence: 99%
“…36 A recent series of 19 patients therapeutically anticoagulated with enoxaparin preoperatively demonstrated the likelihood of residual anti-factor Xa activity, even if the 24-hour interval is maintained. 106 Eleven of 19 patients still had anti-factor Xa activity that would place them at or above the lower limit for the peak target therapeutic range for VTE prophylaxis. One of these patients had an anti-factor Xa level within the target therapeutic range for thrombosis treatment.…”
Section: Therapeutic (Off-label) Applicationsmentioning
confidence: 99%
“…108 However, recent reviews have suggested that a reduction in LMWH dose should be made even with CrCl between 30 and 50 mL/min because of the bleeding risk. 107 It is also interesting that many of the patients in the series by Henshaw et al, 106 for example, an 85-year-old, 53-kg woman with a calculated CrCl of 45 mL/min, received 60 mg BID. Her anti-factor Xa activity was 0.54 international unit (IU)/mL-still within treatment therapeutic peak target range of 0.5 to 0.8 IU/mL.…”
Section: Therapeutic (Off-label) Applicationsmentioning
confidence: 99%
“…If deciding to monitor LMWH anti-Xa activity before a neuraxial procedure, it is generally accepted to proceed with a level of 0.1 or less. 63 With regard to fondaparinux, German S1-Guidelines suggest that, where neuraxial block is indicated, an anti-Xa activity of 0.1 IU ml À1 or less should be targeted. 150 In patients on fondaparinux wherein there may be a risk of elevated plasma anti-Xa levels, if anti-Xa activity can be monitored, an activity value of 0.1 IU ml À1 or less can be considered a nondetectable anticoagulant effect.…”
Section: Recommendation 23mentioning
confidence: 99%